Advances in Neurobiology and Pharmacology of GPR12 - Allende, Gonzalo; Chávez-Reyes, Jesús; Guerrero-Alba, Raquel; Vázquez-León, Priscila; Marichal-Cancino, Bruno A. (Frontiers in Pharmacology, 2020)
GPR12 is a G protein-coupled orphan receptor genetically related to type 1 and type 2 cannabinoid receptors (CB1 and CB2) which are ancient proteins expressed all over the body. Both cannabinoid receptors, but especially CB1, are involved in neurodevelopment and cognitive processes such as learning, memory, brain reward, coordination, etc. GPR12 shares with CB1 that both are mainly expressed into the brain. Regrettably, very little is known about Physiology of GPR12. Concerning its pharmacology, GPR12 seems to be endogenously activated by the lysophospholipids sphingosine-1-phosphate (S1P) and sphingosyl-phosphorylcholine (SPC). Exogenously, GPR12 is a target for the phytocannabinoid cannabidiol (CBD). Functionally, GPR12 seems to be related to neurogenesis and neural inflammation, but its relationship with cognitive functions remains to be characterized. Although GPR12 was initially suggested to be a cannabinoid receptor, it does not meet the five criteria proposed in 2010 by The International Union of Basic and Clinical Pharmacology (IUPHAR). In this review, we analyze all the direct available information in PUBMED database about expression, function, and pharmacology of this receptor in central nervous system (CNS) trying to provide a broad overview of its current and prospective neurophysiology. Moreover, in this mini-review we highlight the need to produce more relevant data about the functions of GPR12 in CNS. Hence, this work should motivate further research in this field.